DMSO Increases Mutation Scanning Detection Sensitivity of High-Resolution Melting in Clinical Samples. (6th January 2020) - Song, Chen; Castellanos-Rizaldos, Elena; Bejar, Rafael; Ebert, Benjamin L; Makrigiorgos, G Mike
Abstract: BACKGROUND: Mutation scanning provides the simplest, lowest-cost method for identifying DNA variations on single PCR amplicons, and it may be performed before sequencing to avoid screening of noninformative wild-type samples. High-resolution melting (HRM) is the most commonly used method for mutation scanning. With PCR-HRM, however, mutations less abundant than approximately 3%–10% that can still be clinically significant may often be missed. Therefore, enhancing HRM detection sensitivity is important for mutation scanning and its clinical application. METHODS: We used serial dilution of cell lines containing the TP53 exon 8 mutation to demonstrate the improvement in detection sensitivity for conventional-PCR-HRM in the presence of DMSO. We also conducted coamplification at lower denaturation temperature (COLD)-PCR with an extra step for cross-hybridization, followed by preferential denaturation and amplification at optimized critical temperature ( full -COLD-PCR), to further enrich low-level mutations before HRM with or without DMSO, and we used droplet-digital PCR to derive the optimal conditions for mutation enrichment. Both conventional PCR-HRM and full -COLD-PCR-HRM with and without DMSO were used for mutation scanning of TP53 exon 8 in cancer samples containing known mutations and myelodysplastic syndrome samples with unknown mutations. Mutations in other genes were also examined. RESULTS: The detection sensitivity of PCR-HRM scanning increases 2- to 5-fold in the presence of DMSO, depending on mutation type and sequence context, and can typically detect mutation abundance of approximately 1%. When mutation enrichment is applied during amplification with full -COLD-PCR followed by HRM in the presence of DMSO, mutations with 0.2%–0.3% abundance in TP53 exon 8 can be detected. CONCLUSIONS: DMSO improves HRM mutation scanning sensitivity with saturating dyes. When full -COLD-PCR is used, followed by DMSO-HRM, the overall improvement is about 20-fold compared with conventional PCR-HRM.